The behavioural dimension of SME’s owner on affecting the financial decisions - Raharja, Bayu Sindhu; Bachtiar, Nia Kurniati; Aziz, Muhammad Ridhwan Ab (Business: Theory and Practice, 2022)
This research seeks the effect of behavioural and non-behavioural factors of SME’s owners and their business characteristic on the financing decisions. Moreover, this research categorized SMEs owners based on their behavioural aspects on establishing a behavioural mapping in SMEs industry. The sample of this research is the informal SMEs owners in Surakarta, Central Java, Indonesia. In investigating the relationship of the independent variable on financial decision making, this research employed the hierarchical linear multiple regression model (HLMR) and multiple logistic regression (LR). Furthermore, this research employed cluster analysis for building a behavioural mapping in SMEs industry. This study discovered a significant effect of behavioural aspects of SME’s owners on the financing decisions, which is, instead of having significant enforcement on the financing decisions, the non-behavioural aspects were more likely impacted on the SMEs owners’ investment decisions. The finding shows that there are three significant groups of SMEs owners in the Surakarta region. The result of this research gives key insights, mainly to the involved stakeholder to keep the sustainability of the SMEs industry.